A new remarkable and Critically Endangered species of Astyanax Baird & Girard (Characiformes: Characidae) from Chapada Diamantina, Bahia, Brazil, with a discussion on durophagy in the Characiformes - Zanata, Angela M.; Lima, Flávio C.t.; Dario, Fabio Di; Gerhard, Pedro (Zootaxa, 2017)
Astyanax brucutu is described from the rio Pratinha, rio Paraguaçu basin, Bahia, Brazil. The new species is promptly distinguished from other characids by having four, rarely three, robust, rounded, and usualy tricuspid teeth on inner premaxillary series and similar teeth on dentary. The species is furthermore characterized by a series of unusual character states in the Characidae, including head blunt in lateral and dorsal views, longitudinal foreshortening of lower jaw, ventral margin of third infraorbital distinctly separated from horizontal limb of preopercle, leaving a broad area without superficial bones, mesethmoid anteroventrally expanded, and adductor mandibulae and primordial ligament remarkably developed. Analysis of gut contents of adults revealed the almost exclusive presence of crushed shells of tiny gastropods of the family Hydrobiidae. The robust anatomy of jaws, teeth, muscles and associated ligaments are likely adaptations to durophagy, a feeding strategy unusual among characids. Astyanax brucutu is known only from its type locality, an approximately 670 m long, transparent and isolated perennial epigean watercourse surrounded by subterranean or intermittent rivers. The distinctive combination of environmental features characterizing the area of occurrence of the new species is not observed elsewhere in the basin or adjacent basins. A series of severe anthropogenic impacts, associated with the restricted geographic range of the species, implies that A. brucutu should be regarded as Critically Endangered (CR) according to IUCN Red List Criteria.